2005
DOI: 10.1073/pnas.0507693102
|View full text |Cite
|
Sign up to set email alerts
|

A regulator of nutritional copper signaling in Chlamydomonas is an SBP domain protein that recognizes the GTAC core of copper response element

Abstract: The CRR1 (Copper Response Regulator) locus, required for both activating and repressing target genes of a copper-and hypoxiasensing pathway in Chlamydomonas, encodes a 1,232-residue candidate transcription factor with a plant-specific DNA-binding domain named SBP, ankyrin repeats, and a C-terminal Cys-rich region, with similarity to a Drosophila metallothionein. The recombinant SBP domain of Crr1 shows zinc-dependent binding to functionally defined copper-response elements associated with the CYC6 and CPX1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
323
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(342 citation statements)
references
References 40 publications
14
323
2
3
Order By: Relevance
“…The highly conserved SBP DNA-binding domain is a Cys-and His-rich region (consensus: CX 4 CX 13 HX 5 HX-15 CQQCX 3 HX 11 C) found only in proteins from photosynthetic organisms (12,13,18,28). The founding members of the SBP domain gene family (SBP1 and SBP2 from A. majus) were identified by their ability to bind to the upstream regulatory region of the SQUAMOSA floral meristem identity gene (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The highly conserved SBP DNA-binding domain is a Cys-and His-rich region (consensus: CX 4 CX 13 HX 5 HX-15 CQQCX 3 HX 11 C) found only in proteins from photosynthetic organisms (12,13,18,28). The founding members of the SBP domain gene family (SBP1 and SBP2 from A. majus) were identified by their ability to bind to the upstream regulatory region of the SQUAMOSA floral meristem identity gene (29).…”
Section: Discussionmentioning
confidence: 99%
“…The Kinetic Binding Parameters of SBP Domains Differ -The SBP domain DNA binding is dependent on the presence of Zn 2+ ions (18,28). The NMR-resolved structures of SBP domains revealed that the SBP domain forms a novel two Zn structure DNA-binding domain (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Chlamydomonas, this switch is controlled by copper response elements associated with the CYC6 gene encoding Cyt c 6 and a transcription factor, copper response regulator 1 (CRR1) (4 -6). CRR1 has a SQUAMOSA promoter binding protein (SBP) domain that is conserved in the green lineage (6). Its homologue in Arabidopsis, SPL7, controls nutritional copper homeostasis as well (7,8).…”
mentioning
confidence: 99%